DIVERSITY OF ENVIRONMENTAL HEALTH MARKERS ODONATA AND LEPIDOPTERA IN GWARIGHAT REGION OF RIVER NARMADA, JABALPUR (M.P.) INDIA - Painkra, Neelima; Shukla, Arjun; Rai, Shivani (International Journal of Research -GRANTHAALAYAH, 2016)
River Narmada is the fifth largest westwards flowing river of India. Biodiversity protection and conservation is a national and international agenda and responsible for sustainable development of a region or a country and secondly Lepidoptera and Odonata are potential bio control agents of many invertebrates. Lepidoptera and Odonata assemblage along with river Narmada bank of Gwarighat region in Jabalpur has been investigated. A total of 41species have been distributed in two orders Odonata with 22 species and Lepidoptera with 19 species were sampled. Libellulidae with 9 species under order Odonata and Nymphalidae with 9 species under Lepidoptera are the most dominating families while others have fewer representatives. Mostly organisms were aggregated due to habitat specific nature and random distribution indicates availability of resource utilization to survive but, in the urban forest area, high anthropogenic disturbances were observed which creates high biotic pressure on forest. A detailed list of Odonata and Lepidoptera recorded from urban forest area is presented.